411PComparative analysis of protein profiles of prognosis-associated proteins and KIT-related proteins in gastrointestinal stromal tumour. (24th November 2019) - Suehara, Y; Sasa, K; Okubo, T; Hayashi, T; Sano, K; Kurihara, T; Akaike, K; Ishii, M; Kim, Y; Kaneko, K; Saito, T
Abstract: Background: Gastrointestinal stromal tumor (GIST) is a type of mesenchymal tumor and has KIT mutations in 80–90% of the cases. The development of tyrosine kinase inhibitors have greatly improved patient outcomes. We have previously described association between lower pfetin (KCTD12) expression and poor prognosis in the GIST patients (Ref 1. Suenara Y et al. Clin Cancer Res2008). In this study, to investigate the protein profiles of kit expression, we performed comprehensive protein expression analysis using the gastric tumor cell lines and surgical specimens in GIST. Methods: We performed KITgene knockdown using siRNA inthe GIST cell line (T1 cell line) and generated the protein expression profiling data by i-TRAQ. Based on this i-TRAQ protein profiling data from the T1 cell line, we referenced our previously published protein expression analysis databases associated with GIST prognosis in the patient samples (Ref 1.) and compared the protein profile of KIT-associated proteins (T1 cell line) and prognosis-associated protein (patient samples). Results: In our study, the i-TRAQ profiling method detected expression of approximately 1500–2000 proteins. In KITknockdown cells, 125 proteins were identified to have statistically different expression (p < 0.05). Based on our previously published GIST prognosis protein profile database (using 17 patient tissue samples), 25 proteins were identified to be statistically significant (p < 0.05). Upon comparing the prognosis database with theKIT knockdown database, 6 proteins were identified as common proteins.In particular, the heat shock protein (HSP) 90-beta, which has been previously shown to contribute to the growth of cancer cells, was identified as a critical protein in the biological behavior of GIST. Conclusions: HSP 90-beta is currently considered as a therapeutic target for HSP 90 inhibitors against imatinib-resistant GIST. Our data suggests that the differentiation and cell growth of GIST may be enhanced by the identified proteins, which are in turn induced by KIT. We believe that our established protein profile data will help in improving the understanding of malignant behaviors in GIST. Clinical trial identification: HSP 90-betaplay an important role in the tumor progression of GISTs. Legal entity responsible for the study: Juntendo University. Funding: This study was supported by Grant-in-Aid from the Japan Society for the Promotion of Science (JSPS) KAKENHI (Grant Number #19K22694, #19H03789 and #15KK0353 to Y.S. ; #17K08730 to T.S.; #17K10987to K.K.; #19K16753 to K.A.; #18K15329 to T.O., # 18K16634 to Y.K.) and Leading Advanced Projects for Medical Innovation (LEAP) (Grant Number # JP18am0001009) and the Practical Research for Innovative Cancer Control (Grant Number # JP18ck0106252) from the Japan Agency for Medical Research and Development. Disclosure: All authors have declared no conflicts of interest.